P118 Inflammatory Bowel Disease Unclassified and Ulcerative Colitis: different outcomes? Multicenter case-control study (Spanish ENEIDA registry). (21st January 2022) - Gonzalez Vivo, M; Urpí Ferreruela, M; Castro Senosiain, B; Pérez-Martínez, I; Barrio, J; Codesido Prado, L; Caballol Oliva, B; Pedrera Roman, V; Piqueras Cano, M; Rodríguez Moranta, F; Casanova González, M J; Ramos, L; et al.
Abstract: Background: Patients with inflammatory bowel disease (IBD) are often classified as ulcerative colitis (UC) and Crohn's disease (CD). However, in some cases this categorization is not possible and these patients are labelled as inflammatory bowel disease unclassified (IBDU) -or indeterminate colitis if histologic analysis of surgical specimens is possible-.The aims of this study were to compare the prognosis and therapeutic requirements in patients with IBDU and UC, and to identify potential predictive factors of reclassification as UC or CD. Methods: Retrospective, observational, multicenter and case-control study of Spanish ENEIDA registry promoted by GETECCU. IBDU patients were identified from 18 centers. Every case of IBDU was matched with 2 patients of ulcerative colitis of the same hospital by sex, age at diagnosis and disease extent (in the patchy colitis subgroup, every case was matched with 1 extensive colitis and 1 left colitis). Results: 231 IBDU patients and 469 UC patients were included. Only 15 IBDU patients met current criteria of indeterminate colitis. In the IBDU group 59.7% patients were males and the mean of age at diagnosis was 43.3 years. Disease extent was distributed in 14 proctitis, 59 left-sided colitis, 87 extensive colitis and 53 patchy colitis. 13.9% had rectal sparing and 31.9% presented ileitis. Thirteen percent were smokers at diagnosis, 5.6% had perianal disease and 15.9% had extraintestinal manifestations. Table 1: baseline characteristics of IBDU and UC group. When comparing IBDU to UC patients, there were no statistical differences between proportion of patients that needed immunosuppressants (35.7% vs 37.7%, p=0.558) and biological therapy (27.3% vs 24.3%, p=0.415). Regarding surgery for medically refractory disease, UC patients had higher surgical rates, although these differences did not reach statistical significance (2.6% vs 0.5%, p= 0.062). Figure 1: immunosuppressants, biological and surgery rates. Overall mortality rates were similar in both groups (5.1% in IBDU vs 2.6% in UC); with only one case related to IBD in IBDU group. During follow-up, 67 IBDU patients (31%) were reclassified (32 UC, 34 CD, 1 indeterminate colitis). 25% of patients were reclassified within 46 months of follow-up (Figure 2: Kaplan-Meier curve of reclassification). Neither clinical, biochemical (C- reactive protein, albumin, hemoglobin) nor endoscopic variable (rectal sparing, ileitis) was associated with change in diagnosis. Conclusion: In clinical practice, there were no statistical differences in prognosis, therapeutic requirements and surgical treatment between IBDU and UC patients. Two thirds of patients remained classified as IBDU during the follow-up. No predictive factors of reclassification have been identified.